Cumulative evidence for relationships between multiple variants of HNF1B and the risk of prostate and endometrial cancers - Yu Tong; Yi Qu; Shiping Li; Fengyan Zhao; Yibin Wang; Dezhi Mu (BMC, 2018)
Abstract Background To provide a synopsis of the current understanding of the association between variants of HNF1B and cancer susceptibility, we conducted a comprehensive research synopsis and meta-analysis to evaluate associations between HNF1B variants and prostate and endometrial cancers. Results Eighteen studies totaling 34,937 patients and 55,969 controls were eligible for this meta-analysis. Four variants showed a significant association with the risk of individual cancer. Strong significant associations were found between rs4430796 A and the risk of both prostate cancer (OR = 1.247, p = 2.21 × 10− 77) and endometrial cancer (OR = 1.217, p = 8.98 × 10− 16); the AA, AG genotypes also showed strong significant associations with the risk of prostate cancer (OR1 = 1.517, p = 4.46 × 10− 22; OR2 = 1.180, p = 0.002). There was a strong significant association between rs7501939 G and the risk of prostate cancer (OR = 1.201, p = 9.31 × 10− 31). Strong significant association was found between rs11649743 G (OR = 1.138, p = 1.08 × 10− 12), rs3760511 C (OR = 1.214, p = 1.57 × 10− 19) and the prostate cancer risk;the GG, AG genotypes of rs11649743 also showed strong significant associations with the risk of prostate cancer (OR1 = 1.496, p = 3.32 × 10− 6; OR2 = 1.276, p = 7.82 × 10− 6). All the cumulative epidemiological evidence of associations was graded as strong. Conclusions Our study summarizes the evidence and helps to reveal that common variants of HNF1B are associated with risk of prostate and endometrial cancer.